Macrodystrophia Lipomatosa: Radiologic-Pathologic Correlation - Upadhyay, Deepika; Parashari, Umesh C; Khanduri, Sachin; Bhadury, Samarjit
Macrodystrophia lipomatosa (MDL) is a rare cause of congenital macrodactyly, characterised by progressive proliferation of all mesenchymal elements, with disproportionate increase in fibro-adipose tissue. It occurs most frequently in lower limbs along the distribution of the medial plantar nerve. MDL presents as localised gigantism of the hand or foot and comes to clinical attention for cosmetic reasons, mechanical problems secondary to degenerative joint disease, or development of neurovascular compression. Here, we report a case of MDL, with altered soft tissue growth due to an earlier surgery, making clinical diagnosis difficult. However, with a complete radio-clinical work-up and review of the history, a provisional diagnosis of MDL was made, which was confirmed by histopathology and during surgery.